Application of Audio Lingual Method in Teaching English to Students - Sholikhah, Yayang Imroatus; Ismilah, Siti; Baron, Rifari (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
In Indonesia, English is a foreign language that is not employed in daily contact. This is undoubtedly a significant barrier for kids in memorizing and comprehending English due to insufficient usage intensity. Facilitating English language acquisition for elementary school pupils is advantageous, as they are at an age conducive to absorbing and retaining linguistic material. The four ways to be presented are the Audio Lingual Method. The objective of implementing this method is to enhance students' English proficiency particularly, and it may be utilized for teaching English to elementary school kids broadly. The employed research method is a literature review study. The findings of this study demonstrate that the Audio Lingual Method facilitates the teaching and learning process for students.